TRAITEMENT BIOLOGIQUE DES EAUX USEES. ETUDE STATIQUE ET DYNAMIQUE - DJAFER Abderrahmane (My University, 2014)
The growing utilization of water by industries, has led to increased wastewater discharges, causing degradation of the receiving environment, thereby affecting aquatic organisms in particular and ecosystems in general. Therefore, treatment of these effluents is essential. Conventional methods of treatment of industrial effluents such as: membrane processes, electrochemical treatment, activated carbon adsorption, are effective for most cases but are very expensive. One alternative to this problem is the use of a biosorbents. The main objective of our work was to study the potential of biomass from a sewage treatment plant for domestic wastewater of Chlef city. We operated for the elimination of two toxic pollutants: hexavalent chromium (Cr (VI)) and bimacid red industrial dye (E5R).The study has conducted in a dispersed medium(batch process) and dynamic(column method) in the grain and pozzolana powder, bentonite and a free and immobilized biomass. The results of removal of the two pollutants showed that the immobilized biomass is more efficient than suspended one. This effectiveness increases with temperature and with the initial concentration of the pollutant in the solution. The Langmuir model simulates better biosorption isotherms and thermodynamic parameters had evaluated. The kinetics of biosorption of Cr(VI) is of order1, while the dye is of order 2. In dynamic mode, the parameters: Feed rates, bed height, initial concentration of the pollutant had studied.
Keywords: Adsorption, chrome, biosorption, column, biomass, dye.